XRISM/Xtend Transient Search (XTS) detected an X-ray flare from an AGN candidate - Yoshimoto, M.; Fukushima, K.; Kanemaru, Y.; Pottschmidt, Katja; et al (The Astronomer's Telegram, 2025)
XRISM/Xtend Transient Search (XTS) detected an X-ray brightening from an X-ray source XRISM J0918-1212 on 2025-05-06 TT. The source position is determined to be (R.A., Dec.) = (139.395, -12.200), with a systematic error of ∼ 40 arcsec. A plausible counterpart is the AGN candidate 2XMMi J091734.9-121159, which is located ∼ 2 arcsec apart from the position of XRISM J0918-1212. All statistical uncertainties in this report will be provided as a 90% confidence level unless stated otherwise. The flare started at 2025-05-06 at ~15:23 TT, reached its peak on 2025-05-06 at ∼ 20:40, and decayed on a scale of t⁽⁻⁰˙⁹ ⁺/⁻⁰˙²⁾. The peak flux is calculated as 6 × 10⁻¹³ erg s⁻¹ cm⁻² (0.4 – 10.0 keV). A systematic error of roughly 20% should be added to the statistical error. Corresponding luminosity is 3 × 10⁴² erg s⁻¹ by assuming that XRISM J0918-1212 is a member galaxy of Hydra A cluster, whose distance is z = 0.05 (∼ 300 Mpc). Although the decaying time scale is ∼ t⁻¹, this event might be a possible tidal disruption event. We derived the above systematic error for the flux by comparing our derived values for the sources detected with XTS in several observations with those for the corresponding X-ray counterparts. We estimated the systematic error for the source position from the separations between the detected sources with the corresponding counterparts in the same field of view
Authors: M. Yoshimoto (Ehime U.), K. Fukushima, Y. Kanemaru, S. Ogawa (JAXA), M. Audard (U. de Geneve), E. Behar (Technion), S. Inoue (Kyoto U.), Y. Ishihara (Chuo U.), T. Kohmura (TUS), Y. Maeda (JAXA), H. Matsumoto (Osaka U.), M. Mizumoto (UTEF), K. Mori (U. of Miyazaki), N. Nagashima (Chuo U.), M. Nobukawa (NUE), H. Noda (Tohoku U.), K. Pottschmidt (UMBC, NASA GSFC, CRESST), M. Shidatsu (Ehime U.), H. Sugai (Chuo U.), T. Takagi (Ehime U.), H. Takahashi (Hiroshima U.), Y. Terada (Saitama U.), Y. Terashima (Ehime U.), Y. Tsuboi (Chuo U.), H. Uchida (Kyoto U.), T. Yoneyama (Chuo U.)